2019
DOI: 10.33940/biomed/2019.12.7
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Medication Errors With Infusion Pumps

Abstract: The risk of medication errors with infusion pumps is well established, yet a better understanding is needed of the scenarios and factors associated with the errors. Our study explored the frequency of medication errors with infusion pumps, based on events reported to the Pennsylvania Patient Safety Reporting System (PA-PSRS) during calendar year 2018. Our study identified a total of 1,004 events involving a medication error and use of an infusion pump, which occurred at 132 different hospitals in Pennsylvania.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(51 citation statements)
references
References 37 publications
0
49
1
1
Order By: Relevance
“…However, wrong infusion rate was considered as a weekly occurring error by the nurses in the present research study, which makes it a more frequent perceived error than found in the study of Mahmood, Chaudhury and Valente [22]. On the contrary, Taylor and Jones stated wrong infusion rate as the most frequent type of medication error [23]. Another study found also wrong dosage and infusion rate as most common types of reported errors during infusion therapy, which is in line with the present studies' ndings [24].…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…However, wrong infusion rate was considered as a weekly occurring error by the nurses in the present research study, which makes it a more frequent perceived error than found in the study of Mahmood, Chaudhury and Valente [22]. On the contrary, Taylor and Jones stated wrong infusion rate as the most frequent type of medication error [23]. Another study found also wrong dosage and infusion rate as most common types of reported errors during infusion therapy, which is in line with the present studies' ndings [24].…”
Section: Discussioncontrasting
confidence: 62%
“…A previous study also revealed that the drug library was a predictor for user acceptance as it helped to prevent medication errors [31]. Taylor and Jones highlighted the importance of the drug library as a safety strategy to prevent wrong dose, wrong infusion rate, and other setting errors [23]. A study on best practices for reducing infusion-associated medication errors stated infusion pump safety and smart pump technology as important strategies [32].…”
Section: Discussionmentioning
confidence: 99%
“…Two of the included studies had a publication year before 2000 [20,21], and more than half of the studies (n = 15) were published in 2010 and later. A majority of the included studies were conducted in Western countries (n = 15) [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36], four were conducted in Asia [20,[37][38][39], two were conducted in Australia [21,40], and one was conducted in Egypt [2]. With regards to study design, most studies were experimental studies (n = 9) [22,24,27,28,30,31,34,37,39] or prospective observational studies (n = 5) [2,20,29,32,40] followed by retrospective studies (n = 3) [21,25,35], qualitative or mixed-methods studies (n = 3) [23,26,33], and cross-sectional studies (n = 2) [36,38].…”
Section: General Characteristicsmentioning
confidence: 99%
“…In that study, the development was used to improve the drop sensor to read droplets more accurately. Furthermore, the related research done by Matthew has investigated the risk of medication errors with infusion pumps [24]. From his study, it can be known that medication orders may have had incorrect or conflicting rates of dose information.…”
Section: Introductionmentioning
confidence: 99%